DEEP BREATHING EXERCISE INTERVENTIONS TO REDUCE DYSPNEA IN PATIENTS WITH CARDIOVASCULAR DISEASE: A RAPID REVIEW - Eriyani, Theresia; Shalahuddin, Iwan; Pebrianti, Sandra; Maulana, Indra (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
Background: Efforts to control the symptoms of shortness of breath in patients with heart disease can be done by practicing breathing techniques. Breathing exercise is a non-pharmacological therapy that can improve the ability of respiratory muscles to improve lung compliance in improving ventilation function and improving oxygenation. Purpose. This literature aims to summarize and explore the potential and level of ease in applying breathing exercises to reduce shortness of breath in patients with cardiovascular disease. Methods: This literature study used a scoping review design based on the PAGER framework. The identification of study results was carried out based on the PRISMA-ScR protocol   . Article searches were conducted through 5 databases, namely EBSCO-hosted Academic Science Complete, PubMed, Sage Journals, ScienceDirect, and Taylor and Francis. Results: A total of 8 studies found this rapid evidence review. The authors used the Randomized Control Trial (RCT) (6), cohort study (1), and quasi experimental study (1) to look at the potential of breathing exercises in reducing dyspnea in patients with cardiovascular disease. Conclusion: The application of breathing exercise interventions has proven useful in improving lung function and activating the parasympathetic system so that it also affects cardiovascular physiological function (systolic TD, diastolic TD, and HR)